Subcellular distribution and life cycle of Epstein-Barr virus in keratinocytes of oral hairy leukoplakia. - Rabanus, J. P. (1991)
The authors investigated the life cycle of Epstein-Barr virus (EBV) in keratinocytes of oral hairy leukoplakia by combining immunohistochemistry. DNA in situ hybridization, and lectin histochemistry with electron microscopy. Diffuse-staining components of the EBV early antigen complex (EA-D), EBV 150-kd capsid antigen (VCA), EBV membrane antigen (gp350/220), and double-stranded DNA were labeled with monoclonal antibodies. An EBV-DNA probe was used to locate EBV DNA. Wheat-germ agglutinin (WGA) was employed to distinguish Golgi-associated compartments. The authors found EBV proteins and EBV DNA only in keratinocytes with apparent viral assembly. In situ hybridization showed EBV DNA in free corelike material and in electron-dense cores of mature nucleocapsids. Monoclonal antibodies to nonspecific double-stranded DNA attached to the same structures and to marginated chromatin. Components of EA-D were dispersed throughout the nuclei but accumulated near condensed chromatin and in 'punched-out' regions of the chromatin. Epstein-Barr virus 150-kd capsid antigen was found only in the nuclei, where it appeared preferentially on mature nucleocapsids. As yet unexplained arrays of intranuclear particles that remained unlabeled with all EBV-specific probes reacted intensely with an antiserum against common papillomavirus antigen. Gp350/220 was detectable in various cellular membrane compartments and was highly concentrated on EBV envelopes in peripheral Golgi-associated secretory vesicles. It was less abundant on the extracellular EBV, indicating that viral membrane antigen partly dissociates from the mature virus. Combined lectin-binding histochemistry and electron microscopy demonstrated for the first time that EBV is processed in the Golgi apparatus, which eventually releases the virus by fusion with the plasma membrane. These results provide insight into the biologic events that occur during complete EBV replication in vivo.